THE INTEGRATED LEARNING METHOD FOR DEVELOPING PRONUNCIATION - Ulugberdieva , Sarviniso (INTERNATIONAL CONFERENCE ON SCIENCE, INNOVATION AND GLOBAL DEVELOPMENT, 2026)
This thesis discusses the integrated learning method as an effective way to develop English pronunciation skills. It explains how combining listening, reading, writing, and speaking activities helps learners improve sound accuracy, stress, and intonation. The study emphasizes the importance of consistent practice and phonetic awareness. The integrated approach increases students’ confidence and improves overall communication skills.